(untitled) (The International Journal for Scientific Research, 2024)
This qualitative study explored the quality of the tourist experience in Saudi Arabia. A total of 255 tourists who had visited Saudi Arabia in the last six months and had stayed for at least two nights were surveyed using an open-ended questionnaire. The results showed that most of the participants had a positive travel experience and valued the local history and culture of Saudi Arabia. They found the country hospitable with friendly locals and excellent hospitality services. Furthermore, their views on Saudi Arabia changed following their visit, particularly regarding local people. Most participants reported feeling more optimistic about the people of Saudi Arabia after their visit, noting that they were welcoming and kind. Additionally, many participants said that they felt more connected to the culture and history of Saudi Arabia after experiencing it firsthand. They also noted plenty of attractions to explore in Saudi Arabia, from historical sites to modern shopping malls. Overall, the tourists had a positive experience when visiting Saudi Arabia and came away with a greater appreciation for its culture and people. This study is unique as it focuses on the tourists’ perspective of the quality of their experience in KSA.